Ekstraksi Komponen Lipid dari Mikroalga Nannochloropsis oculata dan Nitzschia sp. dengan Metode Sokletasi dan Bligh Dyer: Extraction of Lipid Components from Nannochloropsis oculata and Nitzschia sp. Microalgae with Soxhletation and Bligh Dyer Methods - Stepanus, Jamius Bin (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2023)
Dependence on fossil energy sources as non-renewable energy will trigger the threat of an energy crisis in Indonesia in the future. The solution to this issue is through the development of renewable energy and one of them is through the exploration and utilization of biomass such as microalgae. Microalgae have a high lipid content (4-77%) and have potential as raw materials for producing biofuel (biodiesel, bioethanol, and biogas). Lipids can be converted into biodiesel through acid or base-catalyzed esterification and transesterification reactions. The aim of this research was to determine the percentage of lipid components, namely free fatty acids (FFA), monoglycerides (MAG), diglycerides (DAG), and triglycerides (TAG) from microalgae extracts of Nannochloropsis oculata and Nitzschia sp. using Soxhletation and Bligh Dyer extraction methods. This research also aims to determine the comparison of lipid yields from the two extraction methods. Lipid yield percentage was determined through gas chromatography analysis. The research results showed that the percentages of FFA, MAG, DAG, and TAG for N. oculata ranged from 3.34 - 33.79% (soxhletation) and 0 - 17.54% (bligh dyer). Meanwhile, for Nitzschia sp., the percentage ranged from 7.16 - 26.28% (soxhletation) and 0.45 - 13.73% (bligh dyer). Lipid yield for N. oculata was 1.81% (soxhletation) and 2.21% (bligh dyer), while for Nitzschia sp., 0.96% (soxhletation) and 2.10% (bligh dyer). Based on the results of both extraction methods, it was found that the total lipid percentage of the microalgae N. oculata was higher than Nitzschia sp.